Inhibition of Murine Breast Cancer Metastases by Hydrophilic As4S4 Nanoparticles Is Associated With Decreased ROS and HIF-1α Downregulation - Wang, Tao; Meng, Jie; Wang, Chuan; Wen, Tao; Jia, Mengfan; Ge, Yangyang; Xie, Lifei; Hao, Suisui; Liu, Jian; Xu, Haiyan (Frontiers in Oncology, 2019)
As4S4 is a mineral drug that can be administrated orally and has been applied in the treatment of myeloid leukemia. The aim of this work is to investigate the therapeutic effect of As4S4 in highly metastatic triple-negative breast cancer animal model, as As4S4 has not been applied in the treatment of breast cancer yet. To overcome the poor solubility of original As4S4, a formulation of hydrophilic As4S4 nanoparticles (e-As4S4) developed previously was applied to mouse breast cancer cells as well as the tumor-bearing mice. It was shown that e-As4S4 was much more cytotoxic than r-As4S4, strongly inhibiting the proliferation of the cells and scavenging intracellular reactive oxygen species (ROS). The oral administration of e-As4S4 significantly increased the accumulation of arsenic in the tumor tissue and eliminated ROS in tumor tissues. Besides, e-As4S4 could also inhibit the activation of hypoxia-inducible factor-1α (HIF-1α) and NLRP3 inflammasomes. Consequently, the angiogenesis was reduced, the metastasis to lung and liver was inhibited and the survival of tumor-bearing mice was prolonged. In conclusion, e-As4S4 holds great potential for an alternative therapeutics in the treatment of breast cancer, due to its unique function of correcting the aggressive microenvironment.